2018
DOI: 10.1159/000490131
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR: An Oncogenic Long Non-Coding RNA in Human Cancer

Abstract: Long non-coding RNAs (LncRNAs) represent a novel class of noncoding RNAs that are longer than 200 nucleotides without protein-coding potential and function as novel master regulators in various human diseases, including cancer. Accumulating evidence shows that lncRNAs are dysregulated and implicated in various aspects of cellular homeostasis, such as proliferation, apoptosis, mobility, invasion, metastasis, chromatin remodeling, gene transcription, and post-transcriptional processing. However, the mechanisms b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(146 citation statements)
references
References 145 publications
(144 reference statements)
6
135
0
1
Order By: Relevance
“…23 A previous study has shown that HOTAIR promotes tumor initiation. 24 This can be recapitulated by spheroid formation assays in which ectopic HOTAIR expression in MDA-MB-231/ LZRS-HOTAIR cells promoted mammosphere formation compared to the control cells in suspension culture (Supporting Information Fig. S3A).…”
Section: Resultsmentioning
confidence: 80%
“…23 A previous study has shown that HOTAIR promotes tumor initiation. 24 This can be recapitulated by spheroid formation assays in which ectopic HOTAIR expression in MDA-MB-231/ LZRS-HOTAIR cells promoted mammosphere formation compared to the control cells in suspension culture (Supporting Information Fig. S3A).…”
Section: Resultsmentioning
confidence: 80%
“…It has been widely recognized that HOTAIR plays critical roles in cancer cell proliferation, apoptosis, invasion, metastasis, etc. 28 Expression level of HOTAIR was higher in colon cancer tissue and blood of patients, and was related to higher mortality. 20,21 In addition, HOTAIR was a predictor of metastasis in colon cancer, while the underlying mechanism involved inhibiting E-cadherin and increasing MMP-9 and vimentin expressions.…”
Section: Discussionmentioning
confidence: 98%
“…HOTAIR, which is a well-characterized lncRNA, is upregulated in many cancer types. Studies have demonstrated that HOTAIR played important in promoting cancer progression by regulating gene expression (Tang et al, 2018). HOTAIR guilds EZH2/PRC2 complex to tumor suppressor for triggering gene silencing H3K27me3 (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HOX Transcript Antisense RNA (HOTAIR), as one of the well-studied long non-coding RNA (lncRNA), is significantly overexpressed in multiple cancers with diverse genetic profiles, including both solid and hematopoietic cancers (Tang et al, 2018). HOTAIR drives important cancer phenotypes via inducing deregulations on critical genes by PRC2-mediated H3K27 trimethylation, LSD1/CoREST/REST-mediated H3K4 demethylation and interacting with miRNAs as competitive RNA (Li et al, 2017;Liu et al, 2013;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%